Propensity score matching evaluation of psychological stress and hair cortisol among people living with HIV in China - Xu Chen (Nature Portfolio, 2021)
Abstract To compare the psychological stress level and hair cortisol level of people living with HIV (PLWH) with those without HIV in China, a total of 220 participants were initially enrolled in the study, including 200 PLWH and 20 people living without HIV. Psychological stress level, including quality of life, anxiety, perceived stress and psychological resilience, was self-reported in both groups with related scales. The cortisol in hair was extracted and assessed by LC-APCI-MS/MS method. Propensity score matching analysis was performed to balance the baseline covariates of the two groups, whereas the difference in psychological stress level and hair cortisol level between the two groups was compared. Furthermore, the associations between psychological stress level and cortisol level were examined. Two comparison groups were matched by 1:3 propensity score matching, which yielding 20 people living without HIV and 60 PLWH. Ultimately, in regarding to the psychological stress, the levels of the anxiety (34 vs. 26, p < 0.001), perceived stress (38.5 vs. 33, p = 0.001) and psychological resilience (31 vs. 26, p = 0.004) were higher among PLWH than those living without HIV, but the people without HIV showed higher quality of life (109 vs.116, p < 0. 001). The hair cortisol level (34.66 vs. 21.61, p = 0.002) in PLWH was higher than those living without HIV. However, there were no significant associations between psychological stress level and cortisol level (p > 0.05). The PLWH showed higher level of psychological stress and cortisol than those without HIV. No relationship was seen between psychological stress level and cortisol level in PLWH.